2023
DOI: 10.1038/s41598-023-36876-w
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous AMPA downregulates gamma-frequency network oscillation in CA3 of rat hippocampal slices

Abstract: Pharmacologically-induced persistent hippocampal γ oscillation in area CA3 requires activation of α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionate receptors (AMPARs). However, we demonstrated that exogenous AMPA dose-dependently inhibited carbachol (CCH)-induced γ oscillation in the CA3 area of rat hippocampal slices, but the underlying mechanism is not clear. Application of AMPARs antagonist NBQX (1 μM) did not affect γ oscillation power (γ power), nor AMPA-mediated γ power reduction. At 3 μM, NBQX had no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Following the original implementation of the CA3 model by Neymotin et al [8], our model includes both NMDA and AMPA receptors, and we upscaled the AMPA receptors to simulate the effects of ketamine. However, it should be noted that the impact of the AMPA receptors on γ oscillations is not necessarily straightforward [53], and our model is naturally very simplified. For example, the study conducted by Li et al [53] demonstrated that the application of the synthetic glutamate analog AMPA to CA3 slices ex vivo led to the downregulation of γ oscillation power, but it increased the peak oscillation frequency, and they linked this effect to the modulation of an intracellular signaling pathway impacting neuronal excitability [53].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the original implementation of the CA3 model by Neymotin et al [8], our model includes both NMDA and AMPA receptors, and we upscaled the AMPA receptors to simulate the effects of ketamine. However, it should be noted that the impact of the AMPA receptors on γ oscillations is not necessarily straightforward [53], and our model is naturally very simplified. For example, the study conducted by Li et al [53] demonstrated that the application of the synthetic glutamate analog AMPA to CA3 slices ex vivo led to the downregulation of γ oscillation power, but it increased the peak oscillation frequency, and they linked this effect to the modulation of an intracellular signaling pathway impacting neuronal excitability [53].…”
mentioning
confidence: 99%
“…However, it should be noted that the impact of the AMPA receptors on γ oscillations is not necessarily straightforward [53], and our model is naturally very simplified. For example, the study conducted by Li et al [53] demonstrated that the application of the synthetic glutamate analog AMPA to CA3 slices ex vivo led to the downregulation of γ oscillation power, but it increased the peak oscillation frequency, and they linked this effect to the modulation of an intracellular signaling pathway impacting neuronal excitability [53]. Although this study highlights that AMPAR activation will not necessarily lead to γ power upregulation in all cases, it should be noted that AMPA is not found endogenously to begin with.…”
mentioning
confidence: 99%